A systematic test for myopic loss aversion theory. (24th October 2018) - Costa, Raone Botteon
Abstract : Purpose: Myopic loss aversion, or the combination of loss aversion and frequent portfolio evaluation, has been argued to possibly be one of the factors behind the equity premium puzzle. The purpose of this paper is to offer an alternative systematic test that looks at the relationship between inflation and equity premium to test for this theory. Design/methodology/approach: Inflation and equity premium tends to be positively associated, both in standard rational-agents theoretical models and in simple empirical measures of correlation. Nonetheless, under the presence of nominal return evaluation, behavioral models such as myopic loss aversion do predict a negative causal relationship between those variables. This study aims to check this negative causal relationship. The identification strategy combines elements of two approaches: fixed effects regression on short-term returns and long-term least squares regression. As both methods have different strengths and weaknesses, and use different sources of data variation to compute their estimators, it is argued that the combination of these approaches provides a better identification strategy than each individual method. Findings: This paper finds evidence for a negative relationship between inflation and equity premium in both methods, which supports myopic loss aversion theory. The magnitude of the coefficients is also relevant ranging from −0.23 to −0.80. However, it is also shown that these effects explain only a small part of equity premium observed variation, and are more prevalent in non-industrialized countries, which limits the scope of the theory. Originality/value: The current method for testing myopic loss aversion theory is overly reliant on experimental evidence collected in the lab to estimate behavioral parameters and simulations. The authors complement these by providing an empirical study.